Application and prospect of artificial intelligence in digestive endoscopy. (2nd January 2022) - Zhuang, Huangming; Bao, Anyu; Tan, Yulin; Wang, Hanyu; Xie, Qingfang; Qiu, Meiqi; Xiong, Wanli; Liao, Fei
ABSTRACT: Introduction: With the progress of science and technology, artificial intelligence represented by deep learning has gradually begun to be applied in the medical field. Artificial intelligence has been applied to benign gastrointestinal lesions, tumors, early cancer, inflammatory bowel disease, gallbladder, pancreas, and other diseases. This review summarizes the latest research results on artificial intelligence in digestive endoscopy and discusses the prospect of artificial intelligence in digestive system diseases. Areas covered: We retrieved relevant documents on artificial intelligence in digestive tract diseases from PubMed and Medline. This review elaborates on the knowledge of computer-aided diagnosis in digestive endoscopy. Expert opinion: Artificial intelligence significantly improves diagnostic accuracy, reduces physicians' workload, and provides a shred of evidence for clinical diagnosis and treatment. Shortly, artificial intelligence will have high application value in the field of medicine.